2021
DOI: 10.22342/jme.12.1.13270.181-198
|View full text |Cite
|
Sign up to set email alerts
|

Project-Based Mathematics Learning: Fruit Salad Recipes in Junior High School

Abstract: Mathematics learning is associated with 21st-century skills such as communication, collaboration, critical thinking in problem-solving, creativity, and innovation. To help students obtain these skills, a learning project was developed through Pendidikan Matematika Realistik Indonesia (PMRI) approach by using fruit salad recipes and collaborative learning based on the Lesson Study for Learning Community (LSLC) system. The primary purpose of this study was to develop fruit salad recipes to assist junior high sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The similarity of this study with the previous is that both use the RME approach and develop/support students' mathematical communication skills. The result showed that this approach could improve their skills and help the student develop ideas in finding concepts independently and in groups (Freudenthal, 1968;Haryani et al, 2015;Rahayu et al, 2021;Thompson & Findlay, 2002). Another difference is that its products are in the form of lesson plans and worksheets, and the topic developed is the material for building flat sides.…”
Section: Assessment Phasementioning
confidence: 99%
“…The similarity of this study with the previous is that both use the RME approach and develop/support students' mathematical communication skills. The result showed that this approach could improve their skills and help the student develop ideas in finding concepts independently and in groups (Freudenthal, 1968;Haryani et al, 2015;Rahayu et al, 2021;Thompson & Findlay, 2002). Another difference is that its products are in the form of lesson plans and worksheets, and the topic developed is the material for building flat sides.…”
Section: Assessment Phasementioning
confidence: 99%
“…This research is a validation study with three parts: preliminary design, experimental design, and retrospective analysis (Hadi, 2021;Rahayu & Putri, 2021). The validation study process can be seen in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Eickholt et al (2019) stated that PjBL is a precise and realistic method for student-centered learning. In mathematics classes, PjBL emphasizes the application of mathematics in an interdisciplinary, holistic approach, integrated with practice and complex problems in the real world, where students must be able to carry out investigations to understand and productoriented (Kokotsaki et al, 2016;Rahayu & Putri, 2021). The projects in PjBL are related to student's culture and daily life problems (Markham, 2011;Jalinus et al, 2017;Eickholt et al, 2019;Oguz-Unver & Arabacioglu, 2014), which financial context is an activity that students experience daily.…”
Section: Figure 7 Framework Financial Literacy In Mathematics Classesmentioning
confidence: 99%